Understanding heterogeneity among individuals who smoke cigarettes and vape: assessment of biomarkers of exposure and potential harm among subpopulations from the PATH Wave 1 Data - Pavel N. Lizhnyak; Brendan Noggle; Lai Wei; Jeffery Edmiston; Elizabeth Becker; Ryan A. Black; Mohamadi Sarkar (BMC, 2022)
Abstract Introduction People who both smoke cigarettes and vape are often considered as a homogenous group even though multiple subgroups may exist. We examined biomarkers of exposure (BOE) and biomarkers of potential harm (BOPH) to differentiate between subgroups of people who smoke and vape based on PATH Study Wave 1 (2013-2014) data. Methods We compared people who only smoke cigarettes everyday (Group A, n = 2442) and people who only vape everyday (Group C, n = 169) against people who smoke and vape segmented into subgroups of people who frequently smoke and vape (Group B1, n = 169), frequently smoke and infrequently vape (Group B2, n = 678), frequently vape and infrequently smoke (Group B3, n = 57), and infrequently smoke and vape (Group B4, n = 66). Eighteen BOEs (representing exposure to TSNAs, nicotine, heavy metals, PAHs, and volatile organic compounds) and four BOPHs (representing inflammation and oxidative stress) were compared within the subgroups. Results Levels of many BOEs/BOPHs were higher among Group B2 relative to Groups B1, B3, and B4. Compared to Group A, many BOEs were significantly lower in Groups B3 (15/18) and B4 (17/18), and some BOEs were higher among B2 (4/18). Compared to Group C, significantly lower BOEs were observed for Group B4 (2/18). Conclusions Overall, the levels of BOEs and BOPHs in people who smoke and vape are associated with frequency of cigarette smoking. Our findings indicate that not all people who smoke and vape are the same, and tobacco product use frequency should be considered when categorizing people who smoke and vape.